2014
DOI: 10.1158/1078-0432.ccr-13-3328
|View full text |Cite
|
Sign up to set email alerts
|

An Integrative Analysis of the Tumorigenic Role of TAZ in Human Non–Small Cell Lung Cancer

Abstract: Purpose: TAZ, also known as WWTR1, has recently been suggested as an oncogene in non-small cell lung cancer (NSCLC). We investigated the clinical relevance of TAZ expression and its functional role in NSCLC tumorigenesis.Experimental Design: We characterized TAZ at the DNA (n ¼ 192), mRNA (n ¼ 196), and protein levels (n ¼ 345) in an NSCLC patient cohort. Gene expression analysis was complemented by a meta-analysis of public datasets (n ¼ 1,382). The effects of TAZ on cell proliferation and cell cycle were ana… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
100
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(102 citation statements)
references
References 51 publications
2
100
0
Order By: Relevance
“…Further experimentation with WWTR1 / TAZ knockdowns resulted in decreased lung tumor progression, while constitutively active WWTR1 / TAZ was found to be sufficient to drive lung tumor progression [40]. Additionally, higher TAZ expression levels in lung tumors have been shown to be predictive of worse prognoses [41, 42]. …”
Section: Discussionmentioning
confidence: 99%
“…Further experimentation with WWTR1 / TAZ knockdowns resulted in decreased lung tumor progression, while constitutively active WWTR1 / TAZ was found to be sufficient to drive lung tumor progression [40]. Additionally, higher TAZ expression levels in lung tumors have been shown to be predictive of worse prognoses [41, 42]. …”
Section: Discussionmentioning
confidence: 99%
“…To investigate the mechanisms by which ABL kinases promote NSCLC metastasis, we carried out GSEA of the altered transcriptome induced by inactivation of the ABL kinases in PC9, PC9M, and H358 NSCLC cells. We found that pharmacological inhibition or knockdown of the ABL kinases markedly reduced the WNT/β-catenin ( Figure 5A and Supplemental Figure 6A) and TAZ ( Figure 5B and Supplemental Figure 6B) pathway signatures (18,27,28).…”
Section: Abl Kinases Promote Expression Of Genes Implicated In Nsclc mentioning
confidence: 93%
“…The full texts of 37 articles were reviewed for more details and an additional 23 studies were excluded for insufficiency of survival data. Finally, 14 articles5,719 meeting the inclusion criteria were included. The study by Yuen et al included survival analyses for two different cohorts 12.…”
Section: Resultsmentioning
confidence: 99%